Factorial identity question

Paul245

$\frac{2 i}{(2 i + 1)!}$ = $\frac{1}{(2 i)!}$ - $\frac{1}{(2 i + 1)!}$

Could anybody please show what it is that needs to be done on LHS to get to RHS in this identity.

coolul007

Gold Member
$\frac{2 i}{(2 i + 1)!}$ = $\frac{1}{(2 i)!}$ - $\frac{1}{(2 i + 1)!}$

Could anybody please show what it is that needs to be done on LHS to get to RHS in this identity.
(2i + 1)! = (2i+1)(2i!)

Paul245

$\frac{2i}{(2i+1)!}$=$\frac{2i}{(2i+1)(2i)! }$
=$\frac{2i}{2i(2i)! + (2i)! }$
= $\frac{2i}{2i(2i)! + 2i (2i - 1)! }$
= $\frac{1}{(2i)! + (2i - 1)! }$

and now what?

acabus

$\frac{2i}{(2i+1)!}$=$\frac{2i}{(2i+1)(2i)! }$
=$\frac{2i}{2i(2i)! + (2i)! }$
= $\frac{2i}{2i(2i)! + 2i (2i - 1)! }$
= $\frac{1}{(2i)! + (2i - 1)! }$

and now what?
Nah, you've gone at that the wrong way.

Start with the question, and use coolul007's hint to get a common denominator on the right hand side.

Sourabh N

Another way to go about: Add and subtract 1 in the numerator and club 2i and 1.

Paul245

thanks acabus, all

Physics Forums Values

We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling
We Value Civility
• Positive and compassionate attitudes
• Patience while debating
We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving